2011
DOI: 10.1007/s11605-011-1589-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Differences in Repopulation and Early Tumor Response to Preoperative Radiotherapy in Rectal Cancer Patients

Abstract: Accelerated repopulation was noticed in slowly proliferating tumors in females about 4 weeks after RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…The staining intensity of the epidermal growth factor receptor (EGFR) produced a similar kinetic pattern, and the histological results were notably matched with the kinetics of clonogenic tumor cell repopulation. Several other animal models, including mouse fibrosarcoma and mouse ovarian tumor (20,21), and clinical studies based on human breast carcinoma and rectal cancer (22,23), also revealed similar results that Ki-67, BrdUrd labeling indices or SPF decreased initially and increased again at a later time during the course of radiotherapy. Again, the histological results were consistent with the kinetics of clonogen repopulation.…”
Section: Demonstration Of Tumor Repopulation During Radiotherapysupporting
confidence: 52%
“…The staining intensity of the epidermal growth factor receptor (EGFR) produced a similar kinetic pattern, and the histological results were notably matched with the kinetics of clonogenic tumor cell repopulation. Several other animal models, including mouse fibrosarcoma and mouse ovarian tumor (20,21), and clinical studies based on human breast carcinoma and rectal cancer (22,23), also revealed similar results that Ki-67, BrdUrd labeling indices or SPF decreased initially and increased again at a later time during the course of radiotherapy. Again, the histological results were consistent with the kinetics of clonogen repopulation.…”
Section: Demonstration Of Tumor Repopulation During Radiotherapysupporting
confidence: 52%
“…Sex disparities in the prognosis in favor of the female subpopulation have been reported for other tumor entities such as bladder cancer, non-small cell lung cancer, breast cancer, and soft-tissue sarcoma. 13,17,21,23 The underlying mechanisms of sex-dependent differences in outcome have not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…The details of flow cytometric analysis were described earlier. 9 BrdUrdLI was calculated as a percentage of cells which incorporated BrdUrd. DNA ploidy and SPF were calculated from the DNA profile with Mod-Fit software.…”
Section: Flow Cytometric Analysis and Immunohistochemistrymentioning
confidence: 99%
“…Therefore, prognostic value of selected proteins was assessed: the P53 -tumor suppressor protein, BCL2 -antiapoptotic protein, Ki-67 (MIB1), a marker of cell proliferation, GLUT-1 -a hypoxia-regulated membrane protein glucose transporter-1, allowing the energy-independent transport of glucose across the cell membrane, CD-34 -a protein that indicates endothelial cells of blood vessels and, therefore, determines tumor vascularization and Ku70 -a protein involved in the DNA repair process. Earlier, we studied the pretreatment tumor proliferation rate (bromodeoxyuridine labeling index; BrdUrdLI, S-phase fraction; SPF) 8,9 and expression of six proteins to assess prognostic significance for early tumor response. 10 We showed that higher Ki-67 and lower BCL2 expression were correlated with pathological tumor responses.…”
Section: Introductionmentioning
confidence: 99%